Global climate change impacts on the potential distribution of typical Trachinotus fishes and early warning assessment of invasions - Chen, Shaohua; Xiao, Yongshuang; Xiao, Zhizhong; Li, Jun; Herrera-Ulloa, Angel (Environmental research, 2024)
Marine habitats and ecosystems are increasingly being impacted by global climate change and the global spread of captive breeding. In this study, we focused on five typical Trachinotus species (Trachinotus anak, Trachinotus blochii, Trachinotus mookalee, Trachinotus goreenisi, Trachinotus ovatus) as research subjects. We utilized species distribution models and ecological niche models to predict the present and future potential distribution of these species, as well as to assess ecological niche overlap and evaluate the early warning of invasion by Trachinotus species. T. ovatus stands out with its broad distribution range and high adaptability to different environments. It occupies 1.114% of medium-high suitable areas, spanning 100,147 km2. Our predictions also suggest that T. ovatus would undergo a significant expansion (approximately 55% of the total area) under both past and future environmental scenarios, demonstrating a higher tolerance and adaptability to changes in ambient temperatures. It can be discerned that T. ovatus exhibits strong environmental adaptability, which may potentially lead to biological invasion along the southeastern coast of China. The T. anak, on the other hand, showed a higher expansion trend under high carbon dioxide concentrations (RCP8.5), indicating a certain convergence with carbon dioxide concentration. Our models showed that under future climatic conditions, T. ovatus would become the dominant species, with increased competition with T. mookalee and decreased competition with T. goreenisi, T. mookalee, and T. anak. Based on our findings and the net-pen culture mode of T. ovatus, we identified the hotspot habitat of T. ovatus to be located in the Indo-Pacific convergence zone. However, there is a possibility of an expansion trend towards the southeast coast of China in the future. Therefore, it is crucial to provide an early warning for the potential biological invasion of T. ovatus. [Display omitted] •T. ovatus demonstrates a strong ability to adapt to environmental changes in different habitats.•The Indo-Pacific convergence zone emerged as a hotspot for the species T. anak, T. blochii, and T. ovatus.•The expansion of T. anak was undoubtedly related to CO2 concentrations.•The results clearly indicated the imminent biological invasion of T. ovatus along the southeastern coast of China.